1991
DOI: 10.1086/298261
|View full text |Cite
|
Sign up to set email alerts
|

"Overeducation" in the Labor Market

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
407
3
64

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(490 citation statements)
references
References 13 publications
16
407
3
64
Order By: Relevance
“…Conversely, both assignment theory (Sattinger, 1993) and the job competition model (Thurow, 1975) provide frameworks by which overeducation is understood as a mismatch between the characteristics of workers and the productivity requirements of the available distribution of jobs. Finally, overeducation can also be understood as a temporary issue arising as a consequence of information asymmetries or strategic behaviour by workers seeking more basic skills in their chosen professions, for example, signalling phenomenon (Spence, 1973) and occupational mobility theories (Sicherman, 1991;AlbaRamirez, 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, both assignment theory (Sattinger, 1993) and the job competition model (Thurow, 1975) provide frameworks by which overeducation is understood as a mismatch between the characteristics of workers and the productivity requirements of the available distribution of jobs. Finally, overeducation can also be understood as a temporary issue arising as a consequence of information asymmetries or strategic behaviour by workers seeking more basic skills in their chosen professions, for example, signalling phenomenon (Spence, 1973) and occupational mobility theories (Sicherman, 1991;AlbaRamirez, 1993). …”
Section: Introductionmentioning
confidence: 99%
“…In the US Sicherman (1991) found that around 40% of the workforce were over-educated, while 16% were under-educated. For the UK Sloane et al (1999) found that around 31% of British workers were overeducated, 17% were under-educated and the remainder adequatelyeducated.…”
Section: Introductionmentioning
confidence: 99%
“…Search theory predicts that 2 overeducation should decline with age (experience), while the relation with tenure is ambiguous; the predictions are generally upheld empirically. Human capital theory holds that individuals who are overeducated for their job have made a deliberate investment decision: they choose this job because it provides better than average learning opportunities, which will pay off later in the career (Sicherman, 1991). Our dataset allows to test the latter hypothesis for learning (and pay-off) within the same firm, because the data include records of the individual's career within this firm.…”
Section: Introductionmentioning
confidence: 99%